Henry and Mudge and the long weekend : the eleventh book of their adventures - Rylant, Cynthia; e (New York, NY : Aladdin Paperbacks, 1996)
Henry's and his big dog Mudge's boring weekend becomes interesting when Mom suggests building a castle in the basement.
Level 2: reading with help.
Keywords: Dogs -- Juvenile fiction; Play -- Juvenile fiction